Anterior chest wall non-traumatic diseases: a road map for the radiologist - Guerrini, Susanna; Bagnacci, Giulio; Barile, Antonio; La Paglia, Ernesto; Gentili, Francesco; Luzzi, Luca; Giordano, Nicola; Fioravanti, Antonella; Bellisai, Francesca; Cantarini, Luca; Volterrani, Luca; Frediani, Bruno; et al. (Acta Biomedica Atenei Parmensis, 2020)
The anterior chest wall (AWC) non-traumatic pathologies are largely underestimated, and early detection through imaging is becoming increasingly important. This paper aims to review the major non-traumatic ACW pathologies, with a particular interest in imaging features and differential diagnosis.